2012
DOI: 10.1007/s00534-011-0503-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for organ/space surgical site infection after hepatectomy for hepatocellular carcinoma in 359 recent cases

Abstract: Repeat hepatectomy and bile leakage represent independent risk factors for organ/space SSIs after hepatectomy for HCC. Establishing treatment strategies is important for preventing postoperative bile leakage and reducing the high rate of organ/space SSIs after repeat hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 35 publications
1
28
0
2
Order By: Relevance
“…In other studies, reoperation was also found to be a negative factor related to SSIs. Sadamori et al [31] demonstrated that repeat hepatectomy was an independent risk factor for bile leakage and organ/space SSIs after hepatectomy in hepatocellular carcinoma recurrence. Postoperative infections including SSIs also remain a significant problem among liver transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, reoperation was also found to be a negative factor related to SSIs. Sadamori et al [31] demonstrated that repeat hepatectomy was an independent risk factor for bile leakage and organ/space SSIs after hepatectomy in hepatocellular carcinoma recurrence. Postoperative infections including SSIs also remain a significant problem among liver transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical procedures (Table 1), operative time, intraoperative blood loss, and blood transfusion were recorded as intraoperative outcomes. Details of the surgical techniques of hepatectomy, pancreaticoduodenectomy, and hepatopancreatectomy have been reported previously [11][12][13][14]. At our center, age is not recognized as a contraindication.…”
Section: Clinical Datamentioning
confidence: 99%
“…Details of the surgical techniques have been reported previously [8]. Concerning tumor characteristics, the pathological findings were evaluated in accordance with the rules of the Liver Cancer Study Group of Japan [9].…”
Section: Clinical Datamentioning
confidence: 99%